If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 4 + -5m = -2 + m + -9 Reorder the terms: 4 + 7m + -5m = -2 + m + -9 Combine like terms: 7m + -5m = 2m 4 + 2m = -2 + m + -9 Reorder the terms: 4 + 2m = -2 + -9 + m Combine like terms: -2 + -9 = -11 4 + 2m = -11 + m Solving 4 + 2m = -11 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 4 + 2m + -1m = -11 + m + -1m Combine like terms: 2m + -1m = 1m 4 + 1m = -11 + m + -1m Combine like terms: m + -1m = 0 4 + 1m = -11 + 0 4 + 1m = -11 Add '-4' to each side of the equation. 4 + -4 + 1m = -11 + -4 Combine like terms: 4 + -4 = 0 0 + 1m = -11 + -4 1m = -11 + -4 Combine like terms: -11 + -4 = -15 1m = -15 Divide each side by '1'. m = -15 Simplifying m = -15
| -1+3x=3+9x | | 4=2(g-6) | | 5x-3x=8+2 | | (3x-6)(2x-9)= | | -3+4(x-1)=13x+6-9x | | 7x-3=4x^2-1 | | 5n^2+20n-30=10 | | 2h+6=h+27 | | .425-.42415= | | 13p+5=-3+9p | | 4=2(m-6) | | 2(x+1)+3(2x+3)=0 | | 4a+3s=380 | | 8(z+1)+5(2z+2)= | | -6+4a=-12+6a | | (2x+8)(3x+5)= | | 0.5(x+60)+1.3x=111 | | (-1)(-5)(-6)= | | (f)-2=9x^2-5x+2 | | -4(3n+2)-6(5-n)=-32 | | 3x=17x | | 3(2k-1)=-38 | | x^2-20x+24=0 | | 3(4z-1)-4(z+3)=3(z+1) | | 6-2(x+2)=x-18 | | 6=5z+2 | | -3y-18=-12 | | sprt(4x^2)=0 | | 3(4z-1)4(z+3)=3(z+1) | | 6(1+5x)-x=-100 | | 9x+90=6x+120 | | 3x-x*lnx=0 |